Zooplankton Biodiversity, Lake Size, Isolation and Productivity in the Boundary Waters Canoe Area Wilderness. - Nikolai, Stephen; Faust, Matthew; Troia, Matthew; Zinken, Stephanie (My University, 2009)
This study was conducted in September of 2007 in the Boundary Waters Canoe Area Wilderness to study lake ecology and biodiversity. According to the island biogeography theory, biodiversity will increase with island size and proximity to other land masses. This study was undertaken to determine whether lake size or productivity best predicts zooplanktonbiodiversity. Lake
Zooplankton Biodiversity, Lake Size and Productivity in the Boundary Waters Canoe Wilderness
Color poster with text, images, and graphs describing research conducted by Stephen Nikolai, Matthew Faust, Matthew Troia, and Stephanie Zinken, advised by Todd Wellnitz.
Keywords: Biodiversity--Research; Zooplankton--Minnesota--Boundary Waters Canoe Area; Biodiversity--Minnesota--Boundary Waters Canoe Area; Lake Ecology--Minnesota--Boundary Waters Canoe Area; Habitat (Ecology)--Minnesota--Boundary Waters Canoe Area; Posters